Inovasi Manajemen Retribusi Pasar Melalui Inovasi Tape Pasar di Kota Surakarta - Yunita Ratna Sari (Research and Development Agency Ministry of Home Affairs, 2019)
This study is about managing market retribution using the innovation of “Tape Pasar (Teknologi Aplikasi e-Retribusi Pasar)” in Surakarta City, Central Java. This research is motivated by the existence of market retribution management in 44 traditional markets in Surakarta City which is still done conventionally. Tape Pasar Innovation was initiated by the Surakarta City Trade Office and successfully entered the Top 10 Central Java Public Service Innovation 2018. The aim of this study was to analyze the management of market retribution through Tape Pasar innovation. Through the desk research method, this study utilizes secondary data as a literature source. The results of the study show that Tape Pasar innovation facilitates the management of market retribution. Market retribution management is fast, effective, and efficient in terms of time and human resources (HR). The implementation of Tape Pasar innovations can accelerate the process of market retribution services, especially withdrawal, collection, deposit and recording.